2018
DOI: 10.1186/s13063-018-2472-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of medial humeral epicondyle fractures in children: a structured review protocol for a systematic review of the literature and identification of a core outcome set using a Delphi survey

Abstract: BackgroundMedial humeral epicondyle fractures of the elbow are one of the most common injuries in childhood and often require surgery. There are currently no standardised outcome measures to assess progress after an elbow injury in a child. Wide variation in currently reported outcomes makes comparison of treatment difficult. This study aims to identify outcome measures that have previously been reported in studies evaluating the management of medial epicondyle fractures in children and to facilitate the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Consensus was reached when 70% scored 7-9 and 15% scored 1-3. 9 A recommendation was excluded when 70% scored 1-3 and 15% scored 7-9 or when consensus was not reached after the third voting round. A detailed description of the methods used to develop this guideline and an overview of the results of the voting process can be found in Supplementary Material Document A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus was reached when 70% scored 7-9 and 15% scored 1-3. 9 A recommendation was excluded when 70% scored 1-3 and 15% scored 7-9 or when consensus was not reached after the third voting round. A detailed description of the methods used to develop this guideline and an overview of the results of the voting process can be found in Supplementary Material Document A.…”
Section: Methodsmentioning
confidence: 99%
“…Experts voted by rating their agreement with a recommendation on a nine‐point Likert scale, where ‘1’ meant complete disagreement and ‘9’ meant complete agreement. Consensus was reached when ≥70% scored 7–9 and ≤15% scored 1–3 9 . A recommendation was excluded when ≥70% scored 1–3 and ≤15% scored 7–9 or when consensus was not reached after the third voting round.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring and comparing clubfoot treatment success as well as indications for further intervention is currently hindered by the lack of agreed outcomes by the treating community. Core Outcome Sets (COS), defined as the minimum standardized collection of outcomes to be measured and reported in all research for a specific clinical area, 34 have been developed for several musculoskeletal conditions 35 , 36 but not for clubfoot management. In the absence of a COS we have used the COMET (Core Outcome Measures in Effectiveness Trials) initiative principles 37 to identify the outcome tools reported following Ponseti correction of idiopathic clubfoot and analyze them according to domains and acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of scores will be computed for each outcome and stakeholder group. Determination of consensus for each outcome, by stakeholder group, will be based on definitions used in other COS studies [2124]. Specifically, it will be defined as ≥ 70% participants scoring 7–9 and < 15% scoring the outcome as 1–3.…”
Section: Methodsmentioning
confidence: 99%